2013
DOI: 10.1002/etc.2165
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Fate of Three Novel Brominated Flame Retardants in Aquatic Mesocosms

Abstract: Currently, little is known about the environmental fate and persistence of novel brominated flame retardants (NBFRs). The recent detection of NBFRs in sediment cores and air samples provides insight into their persistence and potential for transport. Limited numbers of laboratory studies have examined the fate and behavior of these compounds, but field-based fate studies have been especially lacking. The authors conducted an aquatic mesocosm experiment to assess the behavior of three NBFRs: bis(tribromophenoxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 32 publications
2
22
0
Order By: Relevance
“…Similarly, the accumulation of TBBPA in fathead minnows from the TBBPA‐BDBPE treatment could be the result of metabolism of TBBPA‐BDBPE or the uptake of TBBPA from the environment. Both options are plausible as TBBPA was detected as an environmental degradation product in our study of NBFR fate in the same mesocosms the following year and cyprinids have demonstrated the ability to cleave ether bonds . However, the formation of TBBPA from TBBPA‐BDBPE in vivo has not been observed before.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Similarly, the accumulation of TBBPA in fathead minnows from the TBBPA‐BDBPE treatment could be the result of metabolism of TBBPA‐BDBPE or the uptake of TBBPA from the environment. Both options are plausible as TBBPA was detected as an environmental degradation product in our study of NBFR fate in the same mesocosms the following year and cyprinids have demonstrated the ability to cleave ether bonds . However, the formation of TBBPA from TBBPA‐BDBPE in vivo has not been observed before.…”
Section: Discussionmentioning
confidence: 83%
“…This strengthens the argument that the DBP was the result of metabolism and was not accumulated from the environment. Also, DBP was not detected as a degradation product in our 2009 environmental fate; however, tribromophenol (TBP) was detected as a degradation product in suspended particulates from these mesocosms treated with the same NBFRs the following year . It is possible that the DBP observed in fathead minnows was the result of accumulation of TBP, followed by a reductive debromination.…”
Section: Discussionmentioning
confidence: 88%
“…The characteristics that allow the assessment of exposure of living organisms to contaminants have been highlighted for many different chemicals such as metals and metalloids (Muller et al, 2003;Smolyakov et al, 2010a,b;Bennett et al, 2012;Correia et al, 2013a;Lagauzère et al, 2013), metal-based nanoparticles (Cleveland et al, 2012;Lowry et al, 2012;Buffet et al, 2013Buffet et al, , 2014, veterinary drug ivermectin (Sanderson et al, 2007), algicide Irgarol (Sapozhnikova et al, 2009), many different pesticides (Bromilow et al, 2006;Pablo et al, 2008), brominated flame retardants (de Jourdan et al, 2013), and petroleum hydrocarbons and polyaromatic hydrocarbons (Yamada et al, 2003;Coulon et al, 2012). Studies of behavior and fate of chemicals and oils, in particular in the event of real spills at sea, have been carried out using flume tanks, the most recent of which allow the reproduction of the height and frequency of waves, the exposure of surface slicks to the recreated spectrum of natural light, and air circulation at the water surface (Centre of Documentation, Research and Experimentation on Accidental Water Pollution, http://www.cedre.…”
Section: Strategies Used For Mimicking a Natural Environmentmentioning
confidence: 99%
“…In addition to the benefits of flame inhibition, one thing they possess in common is their persistence in the environment (de Jourdan et al, 2013). Like their predecessors, they have been found in different environmental compartments Devanathan et al, 2012;Schecter et al, 2010), and also currently generating serious concerns about their effects on the environment and humans (Covaci and Dirtu, 2008;Ogunbayo and Michelangeli, 2007;Schauer et al, 2006).…”
Section: Introductionmentioning
confidence: 99%